Вы находитесь на странице: 1из 17

:

:
.
-
..

2011 .

I.
1.
1. ,

f(x) [a;b] .
. () xOy ,
[a;b] Ox, x = a, x = b y = f(x),
[a;b] .

C
y f (x)

. x = a
x = b

A
a

B
b x

1 ( ).
f(x) 0 , x[a;b] .
S () .

xn 1 n x n

x0 1 x1 2 x2

xi = xi xi1 [xi1 ; xi] , S


= max | [xi1 ; xi] | .

S lim

x
n

f (i )xi
i 1

f ( )x
i

i 1

2 ( ).

v = f(t).
S,
[T1 ; T2] .
.
1) [T1 ; T2] n
t0 = T1 , t1 , t2 , , tn = T2 ( t0 < t1 < t2 < < tn )
2) [ti1 ; ti] (i = 1,2,n) i .
[ti1; ti] , , f(i) .
: f(i) ti , ti = ti ti1 .

S f ( i )ti
i 1

3) = max | [ti1; ti] | .

S lim

f ( )t
i

i 1

2. :

f(x) [a;b] .
.
1) [a;b] n
x0 = a , x1 , x2 , , xn = b ,
x0 < x1 < x2 < < xn .
2) [xi1 ; xi] (i = 1,2,n) i
f(i) xi ,
xi = xi xi1 [xi1 ; xi].
n

I n ( xi , i ) f ( i )xi
i 1

f(x)
[a;b] .

max [ xi 1 ; xi ]
1 i n

I In(xi,i)
0 , >0 >0 ,
[a;b] < ,
i

| In(xi,i) I | < .

In(xi,i) 0,

f(x) [a;b] ( a b).
b

f ( x)dx
a

: [a;b] ,
a b ,
f(x) ,
f(x)dx ,
x .

f(x), [a;b]
, .
1 (
[a;b]).
f(x) [a;b] ,
.
2 (
[a;b]).
, f(x) [a;b] ,
:
1) f(x) [a;b];
2) f(x) [a;b];
3) f(x) [a;b] [a;b]
.

. , a < b .
, :
1) a > b ,
b

f ( x)dx f ( x)dx ;
2) a = b ,
a

f ( x)dx 0 .
a


()
.

3.
1) .
f(x) [a;b] f(x) 0 , x[a;b] ,
b

f ( x)dx S ,
a

S [a;b]
y = f(x).
2)
v = f(t)
t ,
T2

v(t )dt

T1

S,
[T1 ; T2] .

3)

dx b a .
a

4) k (k 0)
, ..
b

kf ( x)dx k f ( x)dx

5)
( )
:
b

f ( x) ( x)dx f ( x)dx ( x)dx


6) [a;b] c
[a;c] [c;b],
b

f ( x)dx f ( x)dx f ( x)dx


a

(1)

. (1) ,
c [a;b], .
7) f(x) > 0 (f(x) 0) x[a;b] ,
b

f ( x)dx 0
a

8) f(x) (x) x[a;b] ,

f ( x )dx 0

f ( x)dx ( x)dx

9) 8 3.
m M
f(x) [a;b],
b

m(b a) f ( x)dx M (b a) .
a

f ( x)dx 0.

10) f(x) ,

f(x) ,

f ( x)dx 2 f ( x)dx.

11) .
f(x) [a;b], (a;b)
c,
b

f ( x)dx (b a) f (c)
a

2.
1. .
-
f(t) [a;b].
f(t) [a;x], a x b .
f(t) [a;x], a x b .
x

f (t )dt
a

f (t )dt ( x) ,
a

D((x)) = [a;b] .

1 ( ).
(x) [a;b],
(x) = f(x) .

2. [a;b]
[a;b] .

: (x) f(x) [a;b] .


F(x) f(x) [a;b] .
F(x) (x)
(. 21 2, I ), ..
x

f (t )dt F ( x) C ,
a

a x b , C .
x = a . (1)
a

f (t )dt F (a) C ,
a

0 = F(a) + C ,
C = F(a) .
, (1)
x

f (t )dt F ( x) F (a) .
a

(1)

x = b :
b

f (t )dt F (b) F (a) .

(2)

(2) .
F(b) F(a)
b

b
a

F (b) F (a) F ( x) a .
.

, (2)
b

f ( x)dx F ( x) a F (b) F (a) .


a

. (2) f(x), F(b) F(a)


.